Leaching behaviour of a sandy soil amended with natural and NH4+ and K+ saturated clinoptilolite and chabazite. Issue 8 (3rd July 2018) - Eslami, Mahboubeh; Khorassani, Reza; Coltorti, Massimo; Malferrari, Daniele; Faccini, Barbara; Ferretti, Giacomo; Di Giuseppe, Dario; Fotovat, Amir; Halajnia, Akram
ABSTRACT: Using saturated or enriched zeolites as slow release fertilizers (SRFs) is considered as an environmental-friendly strategy to enhance use of macronutrients in sandy soils. In this paper, two natural zeolites, clinoptilolite (CLI) and chabazite (CHA) were used as mineral precursors to prepare NH4 + /K + saturated clinoptilolite (NH4 + /K + -CLI) and chabazite (NH4 + /K + -CHA) as zeolitic nutrient sources (ZNSs). Comparison between the nutrient retention capabilities of these ZNSs was one of the main objectives of this study. The NH4 + /K + -CLI and NH4 + /K + -CHA were prepared by soaking the zeolites in NH4 Cl and KCl solutions, respectively. Leaching tests were performed on a sandy soil amended with chemical fertilizers (CFs), NH4 + /K + -CLI and NH4 + /K + -CHA to evaluate the leaching properties of them. The results indicated that approximately 84% and 88% of the NH4 + and K + of soils fertilized with CFs were lost during the experiment, respectively. While, the NH4 + and K + losses from soils amended with NH4 + /K + -CLI and NH4 + /K + -CHA were 29%, 23%, and 14%, 24%, respectively. Despite of drastic changes in leaching behavior of CFs, nutrient losses from ZNSs were more uniform during the experiments. No significant difference was found between the two studied zeolites on reduction of K + loss. However, CHA was more effective in preventing NH4 + loss during leaching.